Hermeneutics as a general methodology of the sciences of the spirit - Betti, Emilio, 1890-1968 (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"With a Foreword by Lars Vinx, this book is the first complete English translation of the Italian jurist, Emilio Betti's classic work Die Hermeneutik als allgemeine Methodik der Geisteswissenschaften, originally published in 1962. Betti's hermeneutical theory is presented here as a 'general methodology of the sciences of the spirit', such as to allow the achievement of objectivity, however relative it might be. Its central focus is the tension between an object, to be considered in its autonomy, and the subjectivity of the interpreter, who can understand the object only by means of his or her own categories, historical-cultural conditions, and interests. Set against the work of Bultmann and Gadamer, Betti is concerned to limit the arbitrariness of subjectivity without diminishing the place of interpretation. Detailing the principles that govern, and therefore, guide any interpretation, Betti traces how interpretation in art and in literature, as well as in the fields of science, jurisprudence, sociology, and economy, can be said to be objective, albeit only ever in a relative sense. This summa of Betti's key contribution to hermeneutic theory will be of interest across a range of disciplines, including legal and literary theory, philosophy, as well as the history and sociology of law"--
Some untidy reflections on Betti-Gadamer debate / Lars Vinx -- Editorial preface / Giorgio A. Pinton -- Hermeneutical problematics in contemporary consciousness -- Objectivations of the spirit -- Representative forms -- Representative function & expressive value -- To interpret and to understand -- The act of interpretation as a triadic process -- Inversion of the creative process and transposition into one another subjectivity -- The directives of interpretation: the canon of the hermeneutical autonomy of the object -- The canon of the coherence of meanings (the principle of totality) -- Analogy and integrative development -- Canon of the actuality of understanding -- Vital rapport with the subject-matter & the direction of the inquiry -- Is it possible to achieve the objectivity of the historical phenomena? -- The function of sensibility for the values proper of the historian: the value-relating interpretation -- The answer to the proposed historical question -- Meaning of a historical phenomenon and its significance in the present -- Dialog and monolog -- Historical interpretation and attribution of an eschatological meaning -- The risk of the denial of objectivity -- Theological hermeneutics and demythologizing of the kerygma -- Recent turn toward the historicity of understanding -- The prejudices as the conditions of the understanding -- Existential foundation of the hermeneutic circle -- The problem of the correctness of the understanding -- Historical understanding as mediation of past and the present -- Claim of a practical application of interpretation -- The mentioned claim is justified only if the interpretation is normatively oriented -- Canon of the hermeneutical correspondence of meaning (adequation of meaning in understanding) -- The character as a work of historical forms of life proposes a problematics of the higher grade -- The technical morphologic interpretation in rapport to the prospected problems of formation -- Context of meanings & styles as products of the autonomy of the spiritual human faculties.
"Routledge Focus" -- taken from front cover.
"A GlassHouse Book" -- title page.
Originally published in German by J.C.B.Mohr, 1962.
OCLC-licensed vendor bibliographic record.
Keywords: Humanities -- Methodology; Hermeneutics; LAW / General; LAW / Jurisprudence; LAW / Legal Writing